PENGARUH KUALITAS PELAYANAN, HARGA DAN CITRA MEREK TERHADAP LOYALITAS KONSUMEN PADA PIZZA HUT JALAN SISINGAMANGARAJA - Alfra Wanda; Husni Muharram Ritonggo; Hernawati Lubis (Ensiklopedia Education Review, 2022)
This study aims to determine whether the quality of administration, cost and overall brand image affect buyer loyalty at Pizza Cottage Jalan Sisingamangaraja. The information inspection procedure used is a cooperative quantitative strategy with the help of the SPSS program. This study used multiple direct recurrences. The examination test was 62 respondents. Lots of important information using polls. The results showed that the quality of assistance more or less influenced the determination of buyers at Pizza Hovel Jalan Sisingamangaraja. Cost somewhat affects the dedication of buyers at Pizza Cottage Jalan Sisingamangaraja. Brand image somewhat affects the dedication of buyers at Pizza Cottage Jalan Sisingamangaraja. Administration quality, cost and brand image simultaneously significantly affect buyer dependence at Pizza Hovel Jalan Sisingamangaraja.Keywords: Service Quality, Price, Brand Image And Loyalty.